2014
DOI: 10.1371/journal.pone.0088823
|View full text |Cite
|
Sign up to set email alerts
|

Association between MTHFR Polymorphisms and Acute Myeloid Leukemia Risk: A Meta-Analysis

Abstract: Previous observational studies investigating the association between methylenetetrahydrofolate reductase (MTHFR) polymorphisms and acute myeloid leukemia risk (AML) have yielded inconsistent results. The aim of this study is to derive a more precise estimation of the association between MTHFR (C677T and A1298C) polymorphisms and acute myeloid leukemia risk. PubMed and Embase databases were systematically searched to identify relevant studies from their inception to August 2013. Odds ratios (ORs) with 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…A similar result (OR=0.75; 95 % CI 0.36-1.57) has been reported in another meta-analysis conducted only in Chinese populations [15]. In assessing the risk of AML with the C677T polymorphism, a non-statistically significant positive association was observed in Asian populations with the 677TT genotype (OR=1.12; 95 % CI 0.88-1.42) compared with 677CC [16]. More recently, a casecontrol study conducted in a Chinese population comprising 98 AML cases (both genders, aged 14-76 years) and 2016 [36].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar result (OR=0.75; 95 % CI 0.36-1.57) has been reported in another meta-analysis conducted only in Chinese populations [15]. In assessing the risk of AML with the C677T polymorphism, a non-statistically significant positive association was observed in Asian populations with the 677TT genotype (OR=1.12; 95 % CI 0.88-1.42) compared with 677CC [16]. More recently, a casecontrol study conducted in a Chinese population comprising 98 AML cases (both genders, aged 14-76 years) and 2016 [36].…”
Section: Discussionsupporting
confidence: 84%
“…Although several studies thus far have investigated whether variant genotypes of MTHFR/TS alter the risk of adult leukemia, the findings have generally been inconclusive [14][15][16][17][18]. It has been hypothesized that the risk of leukemia associated with the MTHFR polymorphisms may depend on folate intake [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports demonstrated association between MTHFR C677T polymorphism and cancer (You et al, 2013;Rai, 2014a), whereas others reported contradictory results i.e no association (Ding et al, 2012;Niu et al, 2012). These inconsistent and confusing conclusions can be attributed to several factors like (i) different selection criteria and selection bias might account for the diversity of the results, (ii) folate metabolic pathway is complex pathway and MTHFR is only one of many enzymes involved in the pathway, (iii) the studies with small sample size were included in the meta-analyses and these studies have lower statistical power than those with large sample size and (iv) finally different mechanisms of carcinogenesis of different cancers might due to gene-variant associations vary in different kinds of diseases (Qin et al, 2014). This contradiction suggests that the effect of the C677T polymorphism of MTHFR on the susceptibility to cancer may vary in different cancer type in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Results have been conflicting, with some studies reporting no effect for MTHFR C677T [8,11,12], and others yielding evidence of an effect at least for MTHFR 677TT [9,10]. A meta-analysis between AML and the MTHFR polymorphisms from nine individual case-control studies reported that the OR for the 1298AC genotype was 0.98 (95% CI = 0.85-1.13) compared with the 1298AA genotype, and that for the 677TT genotype was 1.04 (95% CI = 0.87-1.25) compared with the 677CC genotype [17]. Differences in ethnicity, dietary intake, exposure to environmental carcinogens and sample size may be responsible for the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 99%